A novel fibrinogen B beta chain frameshift mutation causes congenital afibrinogenaemia - Zhang, Jian; Zhao, Xiaojuan; Wang, Zhaoyue; Yu, Ziqiang; Cao, Lijuan; Zhang, Wei; Bai, Xia; Ruan, Changgeng (Thrombosis and Haemostasis, 2013)
Congenital afibrinogenaemia is a rare autosomal recessive disorder caused by various mutations within the fibrinogen genes FGA, FGB and FGG. Ins/del mutations in FGB are extremely rare. We report a patient with afibrinogenaemia who suffered from umbilical cord bleeding and repeated bleeding episodes. His plasma fibrinogen levels could not be detected using the Clauss method and immunological methods. Molecular analyses revealed homozygosity in a novel four bases insertion in codon 40 of FGB exon 2 (g. 2833_2834 ins GTTT), which resulted in a truncated 50-residue polypeptide that contained 11 exceptional abnormal residues. In the transient expression experiments, mutant fibrinogen could be detected at higher level than wild-type fibrinogen in COS-7 cell lysates but not in culture media. These results suggest that the homozygous mutation in FGB could be responsible for congenital afibrinogenaemia in this patient. This frameshift mutation could impair fibrinogen assembly and secretion without influencing the protein synthesis.
Keywords: Congenital afibrinogenaemia; FGB gene; frameshift mutation; fibrinogen secretion